'Theirs was the crisis. Ours was the remedy': The Squatting Movements of 1946 in Britain, Canada, and Australia. Issue 3 (December 2019) - Watson, Don
Abstract : Squatting movements erupted in Britain, Canada and Australia during 1946. Frustrated by government inaction in the face of severe housing shortages, homeless families in the three countries defied the civil and military authorities and occupied empty service camps as places to live. This article identifies similarities and differences in the actions of the participants, many of whom were ex-servicemen; what they achieved; the role of public opinion in the events; how the three governments reacted; and how far the squatters influenced housing policies. These squatting movements were important campaigns for the respective communist parties just before the onset of the Cold War. The article explores the relationships between squatters, ex-service organizations and Communists, examines the extent to which activists in the three countries may have influenced each other, and discusses the failed attempts by the CPs to extend the occupations to private property.